Recordkeeping issues arising from the public hearings of the Royal Commission into Institutional Responses to Child Sexual Abuse - Viviane Hessami (Archives & Manuscripts, 2015)
The Royal Commission into Institutional Responses to Child Sexual Abuse was set up in January 2013 to investigate child sexual abuse in institutional contexts and to focus its recommendations on addressing systemic issues. Recordkeeping issues are at the core of the problems that institutions face when dealing with child sexual abuse although the Royal Commission did not address them systematically in 2013–14. The present article analyses the recordkeeping issues that arose in the public hearings held by the Royal Commission up to October 2014. It shows that recordkeeping issues that appeared in different contexts provide evidence of critical failures in the recordkeeping systems of the institutions under study. It then highlights three implications for professional practice: the need for the professional associations to step up and advocate for a hearing on recordkeeping issues, the importance of putting in place appropriate systems to preserve the records of the Royal Commission, and the need to raise awareness about the complexity of the recordkeeping issues in the institutions that deal with out-of-home care and to develop recordkeeping systems that better meet the needs of the children in care and that support the prevention, detection, reporting and prosecution of child abuse.